Does the intervention of mindfulness reduce levels of burnout and compassion fatigue and increase resilience in pre-registration students? A pilot study. Issue 1 (February 2019) - Clarkson, M.; Heads, G.; Hodgson, D.; Probst, H.
Abstract: Introduction: In the current clinical working environment it is important that therapeutic radiography students are fully prepared not just clinically but emotionally for a working professional life. Mindfulness has shown promise, as a self-care strategy, in the improvement of burnout, resilience and compassion fatigue in other professions; however, it has not been used with therapeutic radiography students. Methods: Eight pre-registration therapeutic radiography students were recruited to undergo a five week mindfulness course; six students from the year below were recruited to act as a control arm (no mindfulness). Data was collected using a series of validated tools at baseline, week five, month three and 12 months after the start of the study: 1. The five-facet mindfulness short form questionnaire (FFMQ-SF) 1 2. Maslach Burnout Inventory Student Survey (MBI-SS) 2 3. Professional Quality of Life (ProQOL) 5 questionnaire 3 4. Connor Davidson Resilience-short form scale (CD-RISC) 4 Results: The MBI-SS scale demonstrated 29% of the sample experienced emotional exhaustion and 43% increased cynicism. The other tools showed a positive trend with the intervention; however, these were not statistically significant. Conclusion: Although no statistically significant differences were demonstrated between the study arms, some interesting trends have been noted. The key finding was the identification of burnout experienced by almost a third of the study sample. This suggests that a new area of study is warranted to further investigate the factors contributing to burnout in the student population. Highlights: Development of self-care strategies should start when health care staff begins their training. It is imperative that education institutions address the importance of the potential for burnout in students. Burnout is an issue in student therapeutic radiographers.